Firm life cycle and financial distress: working capital strategy as moderation - Puspita Sari; Iffah Zatil Ismah (Universitas Hayam Wuruk Perbanas, 2023)
This study empirically examines the working capital strategy (WCF) as moderation on the probability of companies experiencing financial distress when viewed from the firm life cycle (FLC). This study uses logistic regression and moderated regression analysis (MRA) to analyze the data and SPSS 24 software to process the data. The study used the sample taken from non-financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period of 2010-2020. The results indicate that the working capital strategy does not moderate the probability of companies experiencing financial distress when viewed from the firm life cycle (FLC). The probability of experiencing financial distress tends to be low in companies that are in the growth and mature phases. Thus, the results of this study confirm the firm life cycle theory.